Prevalence of Anaemia and Its Epidemiological Determinants in Pregnant Women - R.G.Viveki; A.B. Halappanavar; P.R.Viveki; S.B.Halki; V.S.Maled; P.S.Deshpande (Al Ameen Medical College, 2012)
Background: Nutritional anaemia in pregnant women is one of the India's major public health problems, despite the fact that this problem is largely preventable & easily treatable. Objectives: 1.To determine the prevalence of anaemia in pregnant women. 2. To assess the epidemiological determinants of anaemia in pregnancy. Methodology: A descriptive case series study was conducted among the pregnant women from second trimester onwards from urban field practice area from 1st March 2010 to 31st July 2010 by using pre-designed, pre-tested, structured schedule. Haemoglobin estimation was done by Sahli's method & anaemia was graded according to WHO criteria. Statistical analyses were done by percentages and proportions, Mean and Standard Deviation (S.D), Chi-square test. Results: A high prevalence (82.9%) of anaemia (Haemoglobin - < 11.0gm/dl) was observed among 228 pregnant women. Majority (50.4%) had moderate degree of anaemia (Haemoglobin - 7.0 to 10.0 gm/dl) and 7.0% had severe anaemia (Haemoglobin - < 7.0 gm/dl). Severity of anaemia was more in 26 years of age, from nuclear families, educated upto secondary level, having vegetarian diet, parity two or more & those in third trimester with two or more abortions, although statistically not significant. However, anaemia prevalence was significantly higher among those subjects from below Class IV socio-economic status, those with less than two years of spacing between previous and index pregnancies & with less than two months IFA tablet consumption. Conclusion: A very high prevalence of anaemia in pregnancy needs mandatory regular supply of IFA tablets to adolescent and pregnant women from 4th month onwards till 3-6 months post-partum along with correction of other nutritional deficiencies and timely intervention for reducing the burden of related diseases.